2017
DOI: 10.1186/s13017-017-0115-8
|View full text |Cite
|
Sign up to set email alerts
|

A review of the epidemiology and treatment of orthopaedic injuries after earthquakes in developing countries

Abstract: BackgroundEarthquakes in developing countries are devastating events. Orthopaedic surgeons play a key role in treating earthquake-related injuries to the extremities. We describe orthopaedic injury epidemiology to help guide response planning for earthquake-related disasters.MethodsSeveral databases were searched for articles reporting primary injury after major earthquakes from 1970 to June 2016. We used the following key words: “earthquake” AND “fracture” AND “injury” AND “orthopedic” AND “treatment” AND “ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
43
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 23 publications
6
43
0
1
Order By: Relevance
“…The number of patients reaching hospital is not a complete picture of injuries after an earthquake, since many patients were treated by voluntary health workers locally and were not registered. In a review study on earthquake injuries in developing countries, debridement (33%), closed reduction (24%), open reduction and internal fixation (24%) and external fixation (12%) were described as the most common procedures performed [ 4 ]. In our study, more than 300 patients had orthopaedic procedure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The number of patients reaching hospital is not a complete picture of injuries after an earthquake, since many patients were treated by voluntary health workers locally and were not registered. In a review study on earthquake injuries in developing countries, debridement (33%), closed reduction (24%), open reduction and internal fixation (24%) and external fixation (12%) were described as the most common procedures performed [ 4 ]. In our study, more than 300 patients had orthopaedic procedure.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of earthquakes has been reported to be highest in Asia, with China and Pakistan accounting for 40% of all earthquake-related mortality [ 1 ]. Following earthquakes in low-resource settings, health facilities are often damaged and thus the emergency response capacity is reduced [ 1 , 4 ]. A systematic review of earthquakes in developing countries found that lower extremity fractures were the most common type of injury [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The population lockdown was announced on the 17th of March 2020 for eight weeks until the 11th of May 2020. The hospital workload from patients in the emergency department (ED) can vary during exceptional events of various natures in Europe (terrorist attacks (1,2)) and the world (natural disasters (3,4)). While there is precedent for large disasters of natural or human origin in recent history, such as pandemics like H1N1 (5), none have been as long-lasting or as global as the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that earthquakes cause a sharp increase of medical needs due to injuries, many of them requiring surgical and in-hospital treatment 2,27 . Yet, our final analysis showed that, despite an initial peak of admissions on the fifth day after the earthquake, the total number of admissions dropped in the weeks after the earthquake, and slowly increased back to baseline levels after six weeks.…”
Section: Discussionmentioning
confidence: 99%